Significance of caveolin-1 immunohistochemical staining differences in biopsy samples from kidney recipients with BK virus viremia - VELİOĞLU, ARZU (WILEY, 2022)
BK virus infections which usually remains asymptomatic in healthy adults may have different clinical manifestations in immunocompromised patient population. BK virus reactivation can cause BK virus nephropathy in 8% of kidney transplant patients and graft loss may be seen if not treated. Clathrin or Caveolar system is known to be required for the transport of many viruses from Polyomaviruses family including BK viruses. In this study, kidney transplant patients with BK virus viremia were divided into two groups according to the BK virus nephropathy found in kidney biopsy (Group I: Viremia+, Nephropathy+ / Group II: Viremia+, Nephropathy-). Kidney biopsies were examined with immunohistochemical staining to determine the distribution and density of the Caveolin-1 and Clathrin molecules. Immunohistochemical staining of the 31 pathologic specimens with anti-caveolin-1 immunoglobulin revealed statistically significant difference between group-I and group-II. The number of the specimens stained with anti-caveolin-1 was less in group I. On the other hand, we did not find any difference between the groups regarding the anti-clathrin immunochemical analysis. According to these findings, caveolin-1 expression differences in kidney transplant patients may be important in disease progression.
Keywords: BK Virus; caveolin‐ 1; HLA; kidney transplantation